2005
DOI: 10.1016/j.polymer.2004.10.089
|View full text |Cite
|
Sign up to set email alerts
|

Roll-drawing and die-drawing of toughened poly(ethylene terephthalate). Part 1. Structure and mechanical characterization

Abstract: In this work, two solid-state forming processes, namely roll-drawing and die-drawing, were evaluated for inducing high levels of orientation in toughened semicrystalline poly(ethylene terephthalate) (PET), modified with a metallocene ethylene-octene copolymer. In order to study the role of adhesion at the particle/matrix interface, the elastomer was grafted with glycidyl methacrylate (GMA). The GMA functional groups, which can graft to PET to form a copolymer, induced a reduction in the size of the elastomeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Most of the delivered energy was consumed during specimen bending rather than fracture. In contrast to the tensile properties, there was an optimum λ around 5, for which the impact strength was the highest [similar observations were noted for PP and poly(ethylene terephthalate)14–17 and in a review by Galeski18]. Dynamic mechanical measurements showed that rolling to a high strains (>6) produced not only a well‐developed orientation of the crystalline component but also a high orientation and transverse ordering of the amorphous phase, which led to the anisotropy of the material properties in the loading direction/constraint direction plane, perpendicular to the rolling direction.…”
Section: Introductionmentioning
confidence: 55%
“…Most of the delivered energy was consumed during specimen bending rather than fracture. In contrast to the tensile properties, there was an optimum λ around 5, for which the impact strength was the highest [similar observations were noted for PP and poly(ethylene terephthalate)14–17 and in a review by Galeski18]. Dynamic mechanical measurements showed that rolling to a high strains (>6) produced not only a well‐developed orientation of the crystalline component but also a high orientation and transverse ordering of the amorphous phase, which led to the anisotropy of the material properties in the loading direction/constraint direction plane, perpendicular to the rolling direction.…”
Section: Introductionmentioning
confidence: 55%
“…Moreover, it is discovered that these characteristics increase with increasing pre-strain. Furthermore, deformation-induced anisotropy by rolling (Chapleau et al, 2005;Wang et al, 2016;Phua et al, 2011) and extrusion (Tim et al, 2009) have been investigated, where the same results as those obtained from studies regarding anisotropy caused by a uniaxial tensile force were presented. The deformation behavior of deformation-induced anisotropic thermoplastics was visually observed (Shinozaki and Groves, 1973;Brown et al, 1968).…”
Section: Introductionmentioning
confidence: 91%
“…Sun et al [2] and Li et al [3] reported different chain structures of material resulted in the distinct final structure and properties of products even prepared by the same processing method. Chapleau et al [4,5] also reported that the same material via different processing methods had distinct properties. Previous studies has reported that the final structure and morphology not only depend on the inherent characteristic of materials including its chemical composition, molecular weight and distribution, component ratio, and so on [6][7][8][9] but also crucially depend on the structure imparted during various processing conditions [10][11][12].…”
Section: Introductionmentioning
confidence: 99%